2017
DOI: 10.1097/psy.0000000000000426
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Parasympathetic Control and Its Association With Inflammatory Reactivity

Abstract: These findings expand on the current literature by showing that changes in HF-HRV predict and precede changes in circulating inflammatory cytokines in humans and may have implications for treatment of inflammatory diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…After adjusting for age and CAD risk factors, sympatho-vagally mediated HRV remained a significant predictor of CRP. A recent study of 30 young healthy women reported that low vagal tone indicated by reductions in vagally mediated HRV was associated with greater increase in TNF-α and IL-6 but not CRP in response to a speech stressor task ( Woody et al, 2017a ).…”
Section: Stress and The Immune Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…After adjusting for age and CAD risk factors, sympatho-vagally mediated HRV remained a significant predictor of CRP. A recent study of 30 young healthy women reported that low vagal tone indicated by reductions in vagally mediated HRV was associated with greater increase in TNF-α and IL-6 but not CRP in response to a speech stressor task ( Woody et al, 2017a ).…”
Section: Stress and The Immune Systemmentioning
confidence: 99%
“…Albeit mixed ( Owen and Steptoe, 2003 ; Lampert et al, 2008 ), the evidence seems to indicate that prefrontally modulated vagal activity, indicated by vagally mediated HRV is associated with serum levels of pro-inflammatory cytokines ( Sloan et al, 2007 ; von Känel et al, 2007 ; Weber et al, 2010 ; Woody et al, 2017a ), which according to the NISIM is due to lower prefrontal stress regulation capacity resulting in less cholinergic inhibition of inflammatory cytokine production, which in turn results in increased production of TNF-α and IL-6.…”
Section: Stress and The Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…We will limit this discussion to just a few representative studies. Using a stress-inducing paradigm (speech stressor), Woody et al (2017) detected greater reductions in HF-HRV in association with the proinflammatory cytokines, IL-6 and TNFα, but not C-reactive protein (CRP) [44] . Using data from a large study (MIDUS II), Cooper et al (2015) found LF-HRV to be inversely associated with CRP and IL-6 while HF-HRV was inversely associated with fibrinogen and CRP [45] .…”
Section: Discussionmentioning
confidence: 99%